Association Between Alcoholic Cirrhosis and Hemorrhagic Stroke: A Nationwide Population-based Study. (8th April 2019) - Lin, Shih-Yi; Lin, Cheng-Li; Chen, Wei-Shan; Lin, Cheng-Chieh; Lin, Chih-Hsueh; Hsu, Wu-Huei; Hsu, Chung Y; Kao, Chia-Hung
Abstract : This nationwide population based study alcoholic patients with chronic liver disease and cirrhosis (CLDC) had a higher risk of hemorrhagic stroke compared withnon-alcoholic patients with CLDC and patients without CLDC. Abstract: Aims: This study investigated whether patients with alcoholic cirrhosis have a high risk of hemorrhagic stroke. Methods: In this study, 17, 094 patients diagnosed with cirrhosis between 2000 and 2010 were identified using the Taiwan National Health Insurance claims data. Identified patients were randomly selected and propensity score matched with individuals without cirrhosis according to age, sex, comorbidities and index year. Results: The overall incidence rate of stroke was 4.41 and 12.1 per 1000 person-years in the chronic liver disease and cirrhosis (CLDC) with hepatitis B virus (HBV) or hepatitis C virus (HCV) cohort and the alcoholic CLDC cohort, respectively. The alcoholic CLDC cohort exhibited a 4.53-fold higher risk of hemorrhagic stroke (adjusted subhazard ratio [aSHR] = 4.53, 95% confidence interval [CI] = 3.05–6.71) than did the non-CLDC cohort, and the CLDC with HBV or HCV cohort exhibited a 1.40-fold higher risk of hemorrhagic stroke (aSHR = 1.40, 95% CI = 1.10–1.78) than did the non-CLDC cohort. The alcoholic CLDC cohort and the CLDC with HBV or HCV cohort showed an aSHR of 1.80 (95% CI = 1.36–2.40) and 0.95 (95% CI = 0.83–1.07) for ischemic stroke, respectively, compared with the non-CLDC cohort. Conclusion: Alcoholic patients with CLDC had a higher risk of hemorrhagic stroke compared with non-alcoholic patients with CLDC and patients without CLDC.